The Influence of Personal Factors and Situational Factors on Impulse Buying Mediated by Online Trust Among Users of Tiket.com - Aldiano Irzan; Ujang Sumarwan; Doni Yusri (Eduvest - Journal of Universal Studies, 2026)
This study examines the increasing role of digital technology in shaping consumer behavior within the online travel industry, particularly the tendency toward impulse buying among users of online travel agents such as tiket.com. The rapid growth of internet usage and e-commerce in Indonesia has transformed how consumers plan and purchase travel services, often leading to spontaneous purchasing decisions influenced by various internal and external factors. This research aims to analyze the influence of personal factors and situational factors on impulse buying behavior, with online trust as a mediating variable. A quantitative descriptive approach with a cross-sectional design was employed, involving 275 respondents who had previously conducted transactions on tiket.com. Data were collected through online questionnaires and analyzed using Structural Equation Modelling with Partial Least Squares (SEM-PLS). The results indicate that impulse buying tendency, credit card usage, situational conditions, motivational activities, product attributes, scarcity, incidental information, and online trust significantly influence impulse buying. However, shopping pleasure and materialism do not show significant effects. Additionally, online trust successfully mediates the relationship between both personal and situational factors and impulse buying. In conclusion, both internal and external factors play crucial roles in shaping impulsive purchasing behavior, with online trust strengthening these relationships in the context of online tourism platforms.